If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4 + X) = -6 (4 * -1 + X * -1) = -6 (-4 + -1X) = -6 Solving -4 + -1X = -6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1X = -6 + 4 Combine like terms: -4 + 4 = 0 0 + -1X = -6 + 4 -1X = -6 + 4 Combine like terms: -6 + 4 = -2 -1X = -2 Divide each side by '-1'. X = 2 Simplifying X = 2
| 7x+2y+3=36 | | (3x+5)2=144 | | 2k=3.2 | | V(5)=32(5) | | 5(2)x=40 | | 116/200 | | x+15=74 | | 2x-4=-3z+6 | | 5w-16=59 | | 6y+6=3(y+4) | | 400+0.04s=100+0.08s | | z+9=5(4x-2) | | 19x+6y=-39 | | 52xy= | | 4x+7-6x=5-4x-14 | | 3m^2-22+32=0 | | 1/15=x-2/135 | | 48=-16t^2+24t+40 | | 52(x+y)= | | 3(b+2)=3b+2 | | 25-(x/3)=(x/2) | | 75=11+16p | | x+3(-x+1)=9 | | x^2+6x+5=x^2 | | 8t^2=32 | | n+3.01+3n=4n+3.01 | | 7.7=2.7+5x | | 30=3h+6 | | -8c=144 | | m/30=12/72 | | n+-9=-30 | | 2(2x+1)=-1o |